2006
DOI: 10.1002/eji.200636249
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous deletion of MyD88 and Trif delays major histocompatibility and minor antigen mismatch allograft rejection

Abstract: This study investigated whether ablation of all Toll-like receptor (TLR) signaling influenced skin allograft rejection across a complete donor/recipient mismatch of major histocompatibility and minor antigens. We predicted that defective TLR signaling would interfere with the activation of donor dendritic cells (DC) in vivo, by preventing DC activation in response to local environmental ("danger") signals. The ablation of TLR signals would therefore be associated with decreased activation of host T cells and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
61
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 33 publications
8
61
0
Order By: Relevance
“…This finding is in agreement with those of Mckay et al [1] who noted a delay in transplant rejection when MyD88 was absent from donor skin transplants. As acknowledged by the authors, since MyD88 and Trif signaling was intact in recipients, one cannot be sure of the full impact of the dual deletion of Trif and MyD88 signaling during transplant rejection based on their work [1]. This is important since the indirect pathway is sufficient for allograft rejection [4].…”
supporting
confidence: 93%
See 4 more Smart Citations
“…This finding is in agreement with those of Mckay et al [1] who noted a delay in transplant rejection when MyD88 was absent from donor skin transplants. As acknowledged by the authors, since MyD88 and Trif signaling was intact in recipients, one cannot be sure of the full impact of the dual deletion of Trif and MyD88 signaling during transplant rejection based on their work [1]. This is important since the indirect pathway is sufficient for allograft rejection [4].…”
supporting
confidence: 93%
“…In these studies we found that absence of MyD88 impaired the ability of mature DC to accumulate in the draining lymph nodes of transplants both in the minor HY incompatible and the fully MHC mismatched skin transplant model. These results are consistent with the data presented by Mckay et al [1]. In our unpublished findings, we have found that mice with defective Trif signaling (LPS2, the same mice used by Mckay et al [1]) manifest an intact ability to reject HY incompatible skin transplants.…”
supporting
confidence: 93%
See 3 more Smart Citations